Perancangan Sistem Absensi Berbasis Internet of Things (IOT) dengan Fitur Keamanan Sidik Jari - Ilmi, Hayatul; Khairuman, Khairuman; Ginting, Rossiana Br (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Lecturer attendance is an essential aspect in maintaining the quality of the learning process in higher education. Although fingerprint-based attendance technology has been implemented, most existing systems still operate locally and are not yet integrated with the Internet, resulting in the inability to monitor attendance data in real time. This study aims to design and implement a lecturer attendance system based on the Internet of Things (IoT) equipped with a fingerprint security feature, which can automatically and accurately record attendance and display it online through a web-based monitoring interface. The research method used is Research and Development (R&D) with a descriptive qualitative approach. The system design integrates hardware components such as the NodeMCU ESP8266 microcontroller, R307 fingerprint sensor, 16x2 LCD, and buzzer, along with software developed using Arduino IDE and Google Spreadsheet as the online database. The system was tested based on response speed, error rate, and time accuracy parameters. The test results show that the system has an average error rate of 3.3% and an average response time of 2.9 seconds, indicating that the system performs responsively and stably. The fingerprint authentication feature ensures that only registered lecturers can record attendance, while IoT integration enables attendance data to be automatically stored and displayed on the web monitor in real time. Therefore, this system is considered effective, secure, and applicable for supporting academic administration processes in higher education environments.